Retos y desafíos que tiene Colombia en la metodología de vinculación de empleados públicos a la planta de personal frente a la utilizada por la organización de las Naciones Unidas - ONU. como miembro No. 37 de la organización para la Cooperación y el Desarrollo Económico - OCDE. (2022)
Colombia has implemented public contracting policies and methodologies for the staff, through the Civil Service and the National Civil Service Commission - CNSC, which will be compared with the contracting methodologies used in the United Nations - UN , an international organization that is present in 192 countries of the world, and that is a benchmark for social development and community well-being, in order to evaluate and make visible the challenges and / or challenges that the country has in terms of labor, professional and social development and human to its public officials, for this reason the benefits that public employees have and the tranquility that these processes have for the satisfaction of the needs and the impacts that it has on people as members of Colombian society will be investigated.